Analisa Kebocoran Pipa Air Pre Heater Boiler Tipe Circulating Fluidized Bed Combustion Unit-2 pada PLTU 2x30 MW PT. XYZ - Teuku Syamsul Rizal; Teuku Rihayat; Reza Fauzan (Jurnal Teknologi, 2026)
Tube leakage in the air pre-heater system is a critical issue affecting the reliability and efficiency of coal-fired power plants. This study investigates the causes of tube leakage in the air pre-heater of a Circulating Fluidized Bed Combustion (CFBC) boiler Unit-2 at a 2×30 MW power plant of PT. XYZ. The analysis was conducted through dimensional and thickness measurements, visual inspection, and evaluation of operating conditions, including acid dew point calculation and air preheater performance. The results indicate that wall thinning occurs locally and non-uniformly, with minimum thickness reaching 0.00 mm at certain condition, indicating perforation. The inner diameter remains relatively constant, while the outer diameter and wall thickness decrease significantly, suggesting that degradation predominantly originates from the external surface. Visual observations reveal the presence of pitting corrosion, uniform corrosion, and deposit formation on both outer and inner surfaces of the tube. The calculated acid dew point of flue gas ranges from 128.98 to 129.73°C. At low load conditions, the temperature margin between flue gas outlet and acid dew point becomes very narrow, increasing the risk of acid dew point corrosion. In addition, reduced air preheater performance prior to maintenance contributes to the development of a corrosive environment. It is concluded that tube leakage is mainly caused by progressive external erosion-corrosion, with additional contribution from acid dew point corrosion under certain operating conditions. These findings highlight the importance of temperature control, air preheater performance optimization, and periodic thickness monitoring to prevent recurring failures.